Reading Assessment: Higher-Order Thinking Skills (Hots) through ICT - Aisyah Turidho; Dwi Oktalidiasari; Nety Wahyu Saputri (LINGUA: Jurnal Bahasa dan Sastra, 2019)
Abstract: Assessment in English language learning commonly addresses four broad topics; listening, reading, writing and speaking. Reading assessment in learning is very important because it give us information on how students understand the reading and utilize their ability to use the reading. Assessment includes three level namely: low level, medium level and high level. High level reading encompases higher order thinking skills (HOTS). This article aims to examine the relationship between higher order thinking skills (HOTS) in reading assessment and ICT (Information, Communication and Technology). ICT can be used as the media to develop the skills that students must have in HOTS in reading assessment. 21st-century skills require the learning of HOTS which consists of C4 (analyze), C5 (evaluate) and C6 (create). The C4 and C5 are considered critical thinking while C6 is creative thinking. Beside HOTS, ICT is also required in the era of education 4.0 which includes 21st-century skills. Thus, HOTS in reading assessment can be developed using ICT.Keywords: Reading Assessment, HOTS, ICTAbstrak: Assessment dalam pembelajaran bahasa Inggris terdapat empat topik yaitu listening, reading, writing dan speaking. Reading assessment dalam pembelajaran sangat penting untuk memberikan informasi bagaimana siswa memahami suatu bacaan dan memanfaatkan kemampuan mereka dalam menggunakan bacaan. Assessmentterdiri dari tiga level yaitu low level, medium level dan high leveldimana high level inilah yang merupakan higher order thinking skill (HOTS). Artikel kali ini bertujuan untuk mengkaji keterkaitan antara higher order thinking skill (HOTS) dan reading assessment dengan ICT (Information, Communication and Technology). ICT dapat digunakan sebagai media sekaligus kemampuan yang harus dimiliki oleh siswa dalamassesment HOTS matematika. Keterampilan abad-21 mengharuskan pembelajaran dengan pengembangan HOTS didalamnya yaitu critical thinking dan creativity thinking. Ranah kognitif taksonomi bloom dalam HOTS yaitu C4 (analyze), C5 (evaluate) dan C6 (create) dimana C4 dan C5 merupakan critical thinking dan C6 adalah creativity thinking. Selain HOTS, ICT juga merupakan tuntutan dunia pada era pendidikan 4.0 yang termasuk keterampilan abad-21. Sehingga, HOTS dalam reading assesment dapat dikembangkan dengan menggunakan ICT.Kata-kata kunci: Reading Assessment, HOTS, ICT